Outorga de direitos de uso dos recursos hídricos: instituto jurídico-hídrico de implementação ao direito de acesso à água potável - Souza, Manoel Nascimento de (2014)
The water due to its characteristics presents an elementary natural resource that provides the environmental balance and the socioeconomic development of humanity via its multiple uses, which, in our times, when processed deleterious mode has curtailed access to quality water for million people. In watching this anthropic process water use, this study is the analysis scope of the international legal and parental disciplining, the fundamental human right of access to clean water, considering it especially for its implementation objectified by the Brazilian legal system. Therefore, we used as a research method the hermeneutic and systemic held documentary and bibliographic research, it was analyzing respectively the legal and water diplomas and related literature sources to the subject. Thus, the development of this study, it was found that the standardization and implementation of the legal Institute-Water use rights grant of water resources in accordance with the guidelines of the Law of environmental management integration of water with the water and systematic management of water resources with the quantitative and qualitative control of water use, include the structural components of the fundamental human right of access to safe water (quantity, quality and accessibility), ensuring its implementation for present and future generations, as a guarantee, above all, the water inherent dignity of the human being.